Local Government Sustainable Development: A Theoretical Paradigm or a Plan for Action? - Phillips, Janet F.; Strickland, Pamela (Journal of Accounting, Ethics and Public Policy, 2015)
Local governments are a vital component in the national effort to promote sensible methods for community development, growth and social justice. The benefits and challenges of sustainable development have become apparent as more local governments initiate programs to address economic, environmental and social equity issues. This research investigates county and municipal government efforts toward sustainable development using survey information for local governments in the southern United States. Survey responses were analyzed to examine whether local governments “practice what they preach” in terms of actually implementing the sustainable policies proclaimed to be important to their operations. Overall, results suggest local governments do place these policies into action for environmental and social justice issues. In addition, the analysis explores the impact of population size, geographic area and form of government on sustainable development. Measuring the implementation of sustainable policies in terms of dollars, however, proves difficult because there is no consistency among municipalities with regard to reporting the amount of dollars (federal or local) spent in support of sustainability efforts.
Keywords: dept.acc; economic development; environmental protection; local government; peer-reviewed; social equity; sustainability

Accounting Majors Finish First – Results of a Five-Year Study of Performance in Introductory Accounting - Phillips, Janet F. (The Accounting Educators' Journal, 2015)
Delivery of a quality introductory accounting course is essential for schools of business. The first step in revitalization and improvement of the course is to identify factors suggested to be empirically related to succeessful completion. Accounting major status is of particular interest. While it has long been anecdotally observed and logically expected that accounting majors would earn higher grades in introductory accounting, it is rarely addressed in empirical studies. To investigate the impact of accounting major status on performance in introductory accounting, a sample of 398 students exposed to the same professor, text, teaching and examination format over five-years was gathered. Results suggest accounting major status was in fact a significant positive predictor of grades earned in the class controlling for three additional variables (i.e., grade point average, mathematics background and previous experience in the course). These results could be used to support the creation of an honors section(s) of accounting which could include a more rigorous curriculum taught with real life cases. Previous research supported the concept of an honors program from students, faculty and potential employers. In addition, the results suggest requiring a minimum grade point average and the completion of mathematics requirement before taking introductory accounting.
Keywords: dept.acc; peer-reviewed

Indelible Footprints: The ICAN Story - Olutimehin, Kola; Emenyonu, Emmanuel (ICON, 2015)
Keywords: History; History; Accounting; Institute of Chartered Accountants of Nigeria; Nigeria; dept.acc; faculty_collection